2010
DOI: 10.3109/03639045.2010.525238
|View full text |Cite
|
Sign up to set email alerts
|

In vitropercutaneous absorption of genistein from topical gels through human skin

Abstract: The objective of this study was to formulate genistein as a topical gel with various penetration enhancers for increased permeation and retention in human skin. The high performance liquid chromatography assay method was validated for precision and reproducibility. The intra-day and inter-day precision as represented by the coefficient of variation (CV) of the peak areas were <0.44% and <0.67%, respectively. Further, the reproducibility was demonstrated by the CV of the assay at different genistein concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…While it should be pointed out that transcutol (as a skin penetrating vehicle) may form an intracutaneous depot for drugs used in topical formulations (Shokri et al, 2012), it is more likely that the applied equol is sequestered into the epidermal compartment due to the abundance of estrogen receptor subtypes in keratinocytes for which equol has a high affinity (Lephart, 2013a;Lund et al, 2011;Setchell et al, 2005;Thorton et al, 2003). This notion is supported by quantification of the [ 3 H]-equol in the epidermis where the content was higher than typically seen with most other compounds, such as other polyphenolic molecules like resveratrol, the isoflavonoid, genistein, or topical drugs like 17b-estradiol (Chadha et al, 2011;Hung et al, 2008;Xing et al, 2009;Zhong et al, 2009). The reservoir forming properties of equol in the epidermis may be due to its lipophilic characteristics where its octanol-water partition coefficient is 3.20, which is higher than other polyphenolic molecules (Rothwell et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…While it should be pointed out that transcutol (as a skin penetrating vehicle) may form an intracutaneous depot for drugs used in topical formulations (Shokri et al, 2012), it is more likely that the applied equol is sequestered into the epidermal compartment due to the abundance of estrogen receptor subtypes in keratinocytes for which equol has a high affinity (Lephart, 2013a;Lund et al, 2011;Setchell et al, 2005;Thorton et al, 2003). This notion is supported by quantification of the [ 3 H]-equol in the epidermis where the content was higher than typically seen with most other compounds, such as other polyphenolic molecules like resveratrol, the isoflavonoid, genistein, or topical drugs like 17b-estradiol (Chadha et al, 2011;Hung et al, 2008;Xing et al, 2009;Zhong et al, 2009). The reservoir forming properties of equol in the epidermis may be due to its lipophilic characteristics where its octanol-water partition coefficient is 3.20, which is higher than other polyphenolic molecules (Rothwell et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…This indicated that Gel L can facilitate the delivery of diclofenac through the skin when compared to the commercial formulation. The higher flux and K p values observed for diclofenac from Gel L may be related to the faster release of diclofenac and also the penetration enhancing activity of PEG as previously reported [14,45]. In addition, the organogels may have an occlusion effect that enhances the penetration [46,47].…”
Section: In Vitro Release and Skin Permeation Of Diclofenacmentioning
confidence: 57%
“…Accordingly, it might be possible to form a PPR gel based on a low molecular weight (MW) PEG and a β-CD. The advantage of using a low MW PEG is that it can increase the skin permeation [14]. In addition, both PEGs and β-CD are considered to be safe and have been used as excipients in various pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment of skin for 2 h with either oleic acid or α-terpineol as penetration enhancers did not increase the permeation of genistein at pH 6. It was reported that topical delivery was promising for genistein use against photoaging and photodamage, providing a possible application of these gels as skin protection agents for UV-induced damage and chemoprevention of melanoma [47]. …”
Section: The Problem Of Deliverymentioning
confidence: 99%